PENERAPAN MODEL PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR FIQIH DI MTS AL- QUDSIYAH KLOTOK- PLUMPANG - TUBAN - Ana Zumrotul Ainul Ilmiyah; Nur Hasan; Zuhkhriyan Zakariya (VICRATINA, 2021)
The research in this thesis is based on the study of Fiqh in grade VII a MTs Al-Qudsiyah Klotok-Plumpang-Tuban where the results of student massage are still low. Researchers try to solve the problem by applying picture and picture models in fiqh learning so as to improve students' learning outcomes.The purpose of this study is to decipher in improving the learning outcomes of cognitive, affective and psychomotor realms using picture and picture models in the Fiqh.The type of research used in this study is class action research. The implementation process includes (1)The planning stage (2)the implementation stage (3)the Observation Stage and (4)the reflection stage.Data collection techniques use observations, tests and documentation. This can be seen from the percentage of students' learning completion in cycle II which reached 94%, originally during pre-test before the implementation of learning outcomes is 48%. Student learning outcomes in the affective realm also increasein the percentage of student activity, in cycle I reached 71% increased, cycle II which reached 91%.The results of psychomotor learning also increased, the percentage of students' group learning in cycle II by 82% while in cycle I is 45%. Thus it can be concluded that the application of picture and picture models can improve the results of learning in Fiqh subjects in class VIIa MTs Al-Qudsiyah Klotok-Plumpang-Tuban.Kata Kunci: Implementation, Picture and Picture, learning outcomes, Fiqih